2014
DOI: 10.1155/2014/507529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypertension on Neurocognitive Domains in Nondemented Parkinson’s Disease Patients

Abstract: Objective. Health comorbidities, particularly cardiovascular risk factors, are well known to pose risks for cognitive decline in older adults. To date, little attention has focused on the impact of these comorbidities on Parkinson's disease (PD). This study examined the prevalence and contribution of comorbidities on cognitive status in PD patients, above and beyond the effects of disease severity. Methods. A cross sectional design was used, including neuropsychological data on 341 PD patients without severe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 33 publications
2
41
1
Order By: Relevance
“…This finding shows that altered cerebral perfusion secondary to HTN or OH is correlated with decreased cognitive function. Jones et al [24] found that HTN has an influence on executive function and memory recall that goes beyond the deficits produced by the typical PD disease process. They hypothesized that while these deficits are small, they may become more conspicuous and profound as the disease progresses [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding shows that altered cerebral perfusion secondary to HTN or OH is correlated with decreased cognitive function. Jones et al [24] found that HTN has an influence on executive function and memory recall that goes beyond the deficits produced by the typical PD disease process. They hypothesized that while these deficits are small, they may become more conspicuous and profound as the disease progresses [24].…”
Section: Discussionmentioning
confidence: 99%
“…Through single photon emission computed tomography (SPECT), a direct correlation was revealed between hypoperfusion of the posterior association, limbic, posterior cingulate and parietal precuneus cortices (combined score-p = 0.000) in the less affected hemisphere (ipsilateral hemisphere to side of body with prevalence of motor symptoms) and executive function in persons with PD [26]. This adds support to the presence of a "PD Cognitive Pattern (PDCP)" of hypoperfusion described in previous literature and thought to be correlated with a variety of measures of executive function [26] [34]) when compared to those with a diagnosis of PD and "health comorbidities in general" (health comorbidities defined as comorbidities that affected at least 10% of the study population: cholesterol, HTN, hypotension, neurologic, cardiac, arthritis, gastroesophageal reflux disease, cancer, prostate, Roberts syndrome, respiratory, diabetes) (PD + "health comorbidities"-p = 0.146) [24]. The same study also reported the presence of comorbid HTN in persons with PD resulted in decreased scores on tests of executive function (tests of executive function combined score PD + HTN-p = 0.041) compared to persons with PD + OH, PD + OH + HTN, or PD with no other vascular comorbidity [24].…”
Section: Executive Functionmentioning
confidence: 99%
See 3 more Smart Citations